Isaiah Shavitt A Memorial Festschrift from Theoretical Chemistry Accounts - Shepard, Ron; Pitzer, Russell M.; Dunning, Thom (Highlights in Theoretical Chemistry, 2016)
In this Festschrift dedicated to the late Isaiah Shavitt (1925-2012) , selected researchers in theoretical chemistry present research highlights on major developments in the field. Originally published in the journal Theoretical Chemistry Accounts, these outstanding contributions are now available in a hardcover print format, as well as a special electronic edition. This volume provides valuable content for all researchers in theoretical chemistry, and will especially benefit those research groups and libraries with limited access to the journal.